VD_FINDINFO AP / 2011 / 17 vom 17. November 2009 - VD Tribunal cantonal (2009)
ENTREPRENEUR EN RAISON INDIVIDUELLE, DÉFAUT DE LA CHOSE, DEMEURE DU DÉBITEUR | 107 CO, 108 CO, 366 al. 1 CO, 366 al. 2 CO, 366 CO